2016
DOI: 10.1016/j.cellsig.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 influences stress-signalling by reducing the expression of the mTOR-inhibitor REDD1 in a STAT3-dependent manner

Abstract: Abstract:Interleukin 6 is a pleiotropic cytokine and a strong activator of Mammalian Target of Rapamycin (mTOR). In contrast, mTOR activity is negatively regulated by Regulated in Development and DNA Damage Responses 1 (REDD1). Expression of REDD1 is induced by cellular stressors such as glucocorticoids and DNA damaging agents. We show that the expression of basal as well as stress-induced REDD1 is reduced by IL-6. The reduction of REDD1 expression by IL-6 is independent of proteasomal or caspase-mediated degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 62 publications
3
33
0
Order By: Relevance
“…Abnormalities of Ddit4-mediated signaling promote tumorigenesis (Ellisen, 2005;Pineau et al, 2010). Moreover, Ddit4 expression depends on the activation of STAT3 (Pinno et al, 2016). In the present study, Ddit4 was decreased and reversed after rapamycin given, indicating mTORC1 negative feedback on Ddit4.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Abnormalities of Ddit4-mediated signaling promote tumorigenesis (Ellisen, 2005;Pineau et al, 2010). Moreover, Ddit4 expression depends on the activation of STAT3 (Pinno et al, 2016). In the present study, Ddit4 was decreased and reversed after rapamycin given, indicating mTORC1 negative feedback on Ddit4.…”
Section: Discussionsupporting
confidence: 57%
“…Ddit4 is a constant modulator of p-Akt in response to growth factors and nutrients (Dennis et al, 2014), and its expression depends on activation of STAT3 (Pinno et al, 2016). In the present study, LTsc1KO mice demonstrated reduced expression of p-Akt, p-STAT3 and Ddit4 (Figure 5B).…”
Section: Crosstalk Between Mtorc1 and The Stat3 Pathway Was Linked Tosupporting
confidence: 61%
“…These results indicate that REDD1mediated autophagy may be a novel target to sensitize BUC cells to Taxol chemotherapy. REDD1 expression can be induced by MAPK and PKA signaling pathways (42,43), and can also be negatively regulated by other factors such as Ezrin, T-cell acute leukemia 1 (TAL1), and IL6 (44)(45)(46). Here we make the novel discovery that REDD1 is negatively regulated by miR-22.…”
Section: Discussionmentioning
confidence: 98%
“…23 Interestingly, IL-6 can activate mTOR in a STAT3 dependent or independent manner. 24 Whether our proposed drugs can be indeed repurposed for COVID-19 therapies now needs to be carefully tested in in vitro SARS-CoV-2 infection models and in in vivo COVID-19 disease models.…”
Section: Discussionmentioning
confidence: 99%